MISMATCHED FILTERS FOR PROCESSING OF PHASE MANIPULATED SIGNALS WITH THREE-VALUED AUTOCORRELATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The phase manipulated signals, which autocorrelation functions resemble delta pulses, play a very important role for the radars, radio navigation networks and remote control systems as they provide the highest possible resolution of the received signals. Unfortunately, today known classes of such signals have small volumes, which often cannot ensure the necessary electromagnetic compatibility as well as high resistance in a hostile radio electronic environment. Accounting this situation in the paper a method for synthesis of mismatched filters, which effectively suppress the sidelobes of three-valued autocorrelations of phase manipulated signals, is substantiated.